Cellular and Subcellular Localization of the RGS7/Gβ5/R7BP Complex in the Cerebellar Cortex - Aguado, Carolina; Orlandi, Cesare; Fajardo-Serrano, Ana; Gil-Minguez, Mercedes; Martemyanov, Kirill A.; Luján, Rafael (Frontiers in Neuroanatomy, 2016)
A member of regulator of G-protein signalling family, RGS7, is an essential modulator of signalling through GABAB receptors. RGS7 functions as a macromolecular complex with type 5 G protein β (Gβ5) and R7 binding protein (R7BP) to control the localization and function of the resultant heterotrimeric complexes. Here, we used co-immunoprecipitation, in situ hybridization, histoblot and immunohistochemical techniques at the light and electron microscopic level to advance understanding of RGS7-Gβ5-R7BP complexes in central nervous system, focusing on distinct neuronal populations in the cerebellar cortex. Histoblot analysis showed that RGS7, Gβ5 and R7BP proteins were widely expressed in the brain, with mostly an overlapping pattern and showing high expression level in the molecular layer of the cerebellar cortex. Co-immunoprecipitation experiments established that the RGS7/Gβ5 forms complexes with R7BP in the cerebellum. At the cellular level, RGS7 and R7BP mRNAs were expressed at the highest level in Purkinje cells and Golgi cells, and at low levels in granule cells. Immunohistochemistry confirmed that labelling for RGS7, Gβ5 and R7BP were present in the three neuronal populations and concentrated in dendrites and spines. At the electron microscopic level, immunolabelling for RGS7, Gβ5 and R7BP proteins was found both at postsynaptic and presynaptic sites and showed similar distribution patterns. Immunoreactivity for the three proteins was mostly localized along the extrasynaptic plasma membrane of dendritic shafts and spines of Purkinje cells and, to a lesser extent, in axon terminals establishing excitatory synapses. Quantitative analysis of immunogold particles for RGS7, Gβ5 and R7BP revealed that they are non-uniformly distributed along the surface of Purkinje cells, and show enrichment around excitatory synapses on dendritic spines. We further report that deletion of R7BP in mice reduced the targeting of both RGS7 and Gβ5 to the plasma membrane. Altogether, these data support the existence of macromolecular complexes composed of RGS7-Gβ5-R7BP in Purkinje cells. The location at post- and pre-synaptic sites in Purkinje cell spines-parallel fibre synapses suggests their involvement in the modulation of glutamatergic neurotransmission in the cerebellar cortex.